Comparison of Clinical & Laboratory Standards Institute standards in antimicrobial susceptibility among the carbapenemase producing Enterobacteriaceae. (5th October 2017) - Enyinnaya, Fidelis; Cruz, Patricia; Buttner, Mark P; Cross, Chad; Woodard, David R
Aim: Carbapenems are antibiotics reserved for treatment of severe infections. Carbapenem antimicrobial susceptibility testing profiles were determined in a population of Klebsiella pneumoniae, and their resistance assessed based on previous and current Clinical and Laboratory Standards Institute criteria.Materials & methods: Isolates were examined using an automated antimicrobial susceptibility testing method, and real time polymerase chain reaction to detect the resistance ( blaKPC ) gene.Results: The prevalence of blaKPC gene was 45/54 (83.3%). Five isolates that were susceptible under the previous criteria changed to nonsusceptible with the current standards. The overall difference in susceptibility between the standards was 8%.Conclusion: This study shows that the current Clinical and Laboratory Standards Institute criteria may not offer additional benefits in the fight against carbapenem-resistant Enterobacteriaceae . Lay abstract: Carbapenem-resistant Enterobacteriaceae (CRE) are a family of bacteria that can result in deadly infections because they are resistant to most antibiotics. We obtained 54 Klebsiella pneumonia carbapenemase isolates, a type of CRE, and determined which antibiotics were effective against them. Results showed that five isolates that were considered susceptible to an antibiotic under the previous criteria were now considered nonsusceptible with the current standards. This study shows that the current criteria may not offer additional benefits in the fight against CRE infections. Studies such as this one and prudent use of antibiotics should limit the spread of antibiotic resistance.